Risk factors and pregnancy outcomes associated with retinopathy in patients presenting with severe preeclampsia: A retrospective cohort study. Issue 11 (March 2020) - Ye, Lei; Shi, Meng-dan; Zhang, Yan-ping; Zhang, Jia-shuo; Zhu, Cai-rong; Zhou, Rong
Abstract : Abstract: The visual system was reported to be affected in over half of patients with preeclampsia (PE), though fundus examination was performed only among patients complaining of visual symptoms. Delayed diagnosis and treatment of PE-related retinopathy may lead to permanent visual impairment. Therefore, we hypothesize that some clinical or laboratory parameters could predict severity of retinal damage. The aim of the study was to explore the risk factors for retinopathy in severe preeclampsia (sPE) and investigate pregnancy outcomes with different degrees of retinopathy. This retrospective cohort study included women with sPE who underwent ophthalmoscopy and delivered after admission to West China Second University Hospital, between June 2013 and December 2016. Clinical and laboratory characteristics were retrieved from medical records. Patients confirmed with retinopathy were followed up with telephones. Multiple logistic regression analysis was performed to identify risk factors of PE-related retinopathy. Five hundred thirty-four patients were included, of which 17.6% having stage-1/2 retinopathy, 14.6% having stage-3/4 retinopathy, and 67.8% having normal retina. Compared with patients without retinopathy, patients with stage 3/4 retinopathy were more likely to have preterm-birth and low-birth-weight babies. Significant risk factors for stage 3/4 retinopathy in sPE included severe hypertension (odds ratio [OR] 2.24, 95% confidence interval [CI]: 1.10–4.56), elevated white blood cell (WBC) counts (OR 1.88, 95% CI: 1.05–3.35), decreased platelet counts (OR 2.12, 95% CI: 1.07–4.48), lactate dehydrogenase (LDH) concentration of >800 IU/L (OR 2.31, 95% CI: 1.05–5.06), low hemoglobin (HGB) concentrations of <110 g/L (OR 3.73, 95% CI: 1.21–11.47), 24-hour proteinuria of 2 to 5 g (OR 6.39, 95% CI: 2.84–14.39), and >5 g (OR 8.66, 95% CI: 3.67–20.44). This study confirms the association between retinopathy and preterm-birth and low-birth weight in sPE. The risk factors for severe PE-related retinopathy, including severe hypertension, platelet and WBC count, HGB and LDH concentration, and proteinuria, are associated with the development of retinopathy. Routine and repeated fundus examination is recommended for maternal monitoring in sPE. Abstract : Supplemental Digital Content is available in the text